Psychometric properties of the Chinese version of the Emotion Regulation Skills Questionnaire - Xia Ma; Suyan Wang; Mengjie Cui; Hongliang Dai; Jianfeng Hu (Acta Psychologica)
Background: The Emotion Regulation Skills Questionnaire (ERSQ) is a valid and reliable tool to measure level of emotion regulation skills. The present study aims to develop a Chinese version of the ERSQ (C-ERSQ), and further establish its psychometric properties among college students. Methods: A total of 848 college students aged 18–35 years answered questionnaires including demographic questionnaire, C-ERSQ, Emotion Regulation Questionnaire (ERQ), Cognitive Emotion Regulation Questionnaire (CERQ), Difficulties in Emotion Regulation Scale (DERS), and Positive and Negative Affect (PANAS). The construct validity was tested using confirmatory factor analysis (CFA), with multi-group CFA administered for analysis of measurement equivalence. Criterion-related validity was performed against ERQ, CERQ, DERS, and PANAS. Internal consistency Cronbach's α, split-half reliability, test-retest reliability, and composite reliability (ω) were used for reliability assessment. Results: Factor analysis support a two-factor structural model of the C-ERSQ, which presented strict invariance across sex, ethnicity, whether having siblings, and student type. Male students, or those without siblings, or those with elevated academic experience showed higher level of emotion regulation. The C-ERSQ validity was also supported by its correlation with existing scales measuring emotion regulation or mental health. This scale also had satisfactory reliability. Conclusion: The two-factor C-ERSQ performs well in assessing emotion regulation skills among Chinese college students.